Expression of hypoxia inducible factor 1 alpha and its clinical significance in esophageal carcinoma: A meta-analysis - Shao Wu Jing; Jun Wang; Qing Xu (Tumor Biology)
Many studies have analyzed the relationship between hypoxia inducible factor 1 alpha expression and its relation to differentiation, lymph node metastasis, and other clinicopathological variables of esophageal carcinoma, but the results are still inconsistent. This meta-analysis was carried out to explore hypoxia inducible factor 1 alpha in esophageal carcinoma and its correlation with clinicopathological features and prognosis, in order to provide comprehensive reference for clinic. A total of 18 studies including 1566 patients with esophageal squamous cell carcinoma were enrolled. The results showed that compared with para-carcinoma tissue, the expression of hypoxia inducible factor 1 alpha was significantly enhanced (odds ratio = 0.122, 95% confidence interval = 0.074–0.201, p  = 0.000); hypoxia inducible factor 1 alpha was associated with differentiation (odds ratio = 1.458, 95% confidence interval = 1.108–1.920, p  = 0.007), T classification (odds ratio = 0.457, 95% confidence interval = 0.265–0.786, p  = 0.005), lymph node metastasis (odds ratio = 0.337, 95% confidence interval = 0.185–0.614, p  = 0.000), and pathological tumor–node–metastasis stage (odds ratio = 0.362, 95% confidence interval = 0.177–0.740, p  = 0.005), whereas there was no relation to histological grade, lymphatic vessel invasion, blood vessel invasion, 3- to 5-year overall survival and disease-free survival. Patients with hypoxia inducible factor 1 alpha overexpression had poor differentiation, increased depth of tumor invasion, more lymph node metastasis, and late pathological tumor–node–metastasis stage. Hypoxia inducible factor 1 alpha could be an indicator for differentiation, T classification, lymph node metastasis, and pathological tumor–node–metastasis stage, and it is worth further study.